Search for Lorentz invariance and CPT violation with the MINOS far detector. - Adamson, P; Auty, D; Ayres, D; Backhouse, C; Barr, G; Barrett, W; Bishai, M; Blake, A; Bock, G; Boehnlein, D; Bogert, D; Bower, C; et al. (2010)
We searched for a sidereal modulation in the MINOS far detector neutrino rate. Such a signal would be a consequence of Lorentz and CPT violation as described by the standard-model extension framework. It also would be the first detection of a perturbative effect to conventional neutrino mass oscillations. We found no evidence for this sidereal signature, and the upper limits placed on the magnitudes of the Lorentz and CPT violating coefficients describing the theory are an improvement by factors of 20-510 over the current best limits found by using the MINOS near detector.